MALFORMASI VENA PADA PERGELANGAN TANGAN YANG MENYERUPAI KISTA GANGLION: SEBUAH LAPORAN KASUS - Ameria Pribadi; Karina Sylvana Gani; Mitchel Mitchel (Jurnal Akta Trimedika, 2026)
Vascular malformations of the wrist account for 10% of all vascular malformations and can closely mimic benign cystic lesions such as ganglion cysts, often leading to diagnostic errors. Accurate differentiation is critical, as misdiagnosis may result in inappropriate procedures with potential complications. We report the case of a 25-year-old female presenting with a volar wrist swelling for 3 months and initially diagnosed as a ganglion cyst based on clinical and MRI findings. Intraoperatively, surgical excision revealed a highly vascular lesion arising from the cephalic vein, subsequently confirmed as a venous malformation on histopathological examination. No postoperative complications or recurrence were observed during the four months of follow-up. This case underscores the diagnostic pitfalls in distinguishing vascular malformations from ganglion cysts, particularly in the absence of Doppler ultrasonography. Although MRI is a valuable tool, low-flow venous lesions may exhibit imaging features that resemble cystic structures. Previous reports, have also documented similar misdiagnoses where MRI was not performed, emphasizing the limitations of imaging alone. Venous malformations of the wrist can masquerade as ganglion cysts both clinically and radiologically. Incorporating Doppler ultrasonography into the standard evaluation of atypical wrist cysts is essential to prevent misdiagnosis and ensure appropriate management.